Genetic diversity in enhancer II region of HBV genotype D and its association with advanced liver diseases. - Majid Khan; Sanaullah Khan; Mehrunnisa Fatima Gondal; Safia Bibi; Bakht Tarin Khan; Abdul Majid; Ayesha Khattak; Muhammad Nasir Khabir; Muhammad Anwar; Aisha Gul; Maryam Naseem; Sobia Attaullah (PLoS ONE)
Background Hepatitis B Virus (HBV) is one of the most common human infectious agents, and the mutations in its genome may cause chronic hepatitis (CH), liver cirrhosis (LC), and hepatocellular carcinoma (HCC). This study was designed to characterize the enhancer-II (Enh-II) region of X gene in HBV positive patients to assess the association of such mutations with CH, LC, and HCC. Methods HBV positive samples (N = 200) with patients' demographic and clinical data were collected from different regions of Khyber Pakhtunkhwa (KP), Pakistan. The Enh-II region of the HBx gene was sequenced and zanalyzed for polymorphism associated with advanced liver disease. Univariate and logistic regression analyses were performed to evaluate potent mutations associated with a risk for LC and HCC. Results HBV Enh-II region sequences analysis revealed 25 different mutations. The highest frequency of mutations S101F (62.2%), A102V/R/G/I (56.25%), M103L/A (68.75%)were found in HCC, followed in LC and CH patients as 57.1%, 42.8%, 28.52% 16%, 15.2% and 18.4% respectively. H94 deletion in the α-box of the Enh-II region, associated with a high risk of HCC was found in half of the HCC patients. This deletion was present in 28.5% of LC and 6.5% of CH patients. Importantly, the high frequency of some notable mutations such as E109A/Y, A110S/K, Y111D/E, and F112L was first time reported in the entire study population. The frequencies of these mutations were high in HCC (43.75%, 37.5%, 50% and 43.75% respectively) as compared to LC (14.28%, 14.28%, 28.2% and 42.8%) and CH patients (12.8%, 15.2%, 16.8% and 16% respectively). Conclusion Mutations associated with LC and HCC are prevalent in the Enh-II region in Pakistani HBV isolates. The mutations found are alarming in CH patients as these may progress to LC and HCC in a large number of patients.